High Lithium Ion Transport Through rGO-Wrapped LiNi0.6Co0.2Mn0.2O2 Cathode Material for High-Rate Capable Lithium Ion Batteries - Ahn, Wook; Seo, Min-Ho; Pham, Tuan Kiet; Nguyen, Quoc Hung; Luu, Van Tung; Cho, Younghyun; Lee, Young-Woo; Cho, Namchul; Jeong, Soon-Ki (Frontiers in Chemistry, 2019)
In this work, we show an effective ultrasonication assisted self-assembly method under surfactant solution for high rate capable rGO wrapped LiNi0.6Co0.2Mn0.2O2 (Ni-rich cathode material) composite. The ultrasonication indicates pulverization of aggregated bulk material to primary nano particle which is effectively benefit for synthesizing homogeneous wrapped composite with rGO. The cathode composite demonstrates high initial capacity of 196.5 mAh/g and stable capacity retention of 83 % after 100 cycles at a current density of 20 mA/g. The high rate capability shows 195 mAh/g and 140 mAh/g at current density of 50 mA/g and 500 mA/g, respectively. The high rate capable performance is attributed to the rapid lithium ion diffusivity which is confirmed from the calculation of transformation kinetics of lithium ion by Galvanostatic Intermittent Titration Technique (GITT) measurement. The lithium ion diffusion rate (DLi) of rGO wrapped LiNi0.6Co0.2Mn0.2O2 composite is ca. 20 times higher than lithium metal plating on anode during charge procedure, and this is determined from the highly interconnected LiNi0.6Co0.2Mn0.2O2 and conductive rGO sheets in the composite. This unique transformation kinetics study of cathode composite presented in this study is an unprecedented verification example of high rate capable Ni-rich cathode material wrapped by highly conductive rGO sheets.